Cold tolerance mechanisms of two arthropods from the Andean Range of Central Chile: Agathemera crassa (Insecta: Agathemeridae) and Euathlus condorito (Arachnida: Theraphosidae). (May 2018) - Cubillos, Claudio; Cáceres, Juan Carlos; Villablanca, Cristopher; Villarreal, Pablo; Baeza, Marcelo; Cabrera, Ricardo; Graether, Steffen P.; Veloso, Claudio
Abstract: Two strategies have been described for cold tolerance in arthropods: (1) freeze-tolerant organisms, which can survive the formation of ice crystals and (2) freeze-avoidant organisms, which prevent the ice crystal formation by super cooling their internal fluids. We studied two arthropods from the Andean Range in central Chile (2400 m a.s.l.), the stick insect Agathemera crassa commonly named as "Chinchemolle", and the tarantula spider Euathlus condorito commonly named as "Araña pollito", in order to evaluate how they respond to low temperatures at the physiological and molecular levels. We sampled the soil temperature during one year to track the temperature changes that these organisms must overcome. We found minimum temperatures around −6 °C in autumn, while the temperature were stable at 0 °C in winter due to the snow. The average field-cooling rate was 0.01 ± 0.006 °C min −1 . For both arthropods we determined the super cooling point (SCP) at a cooling rate of 1 °C min −1 and its subsequent survival, finding that A. crassa is a freezing tolerant organism with a SCP of −3.8 ± 1.8 °C and 100% survival, while E. condorito is a freezing avoidant organism with a SCP of −3.0 ± 1.3 °C and 0% survival. The SCP and survival were not affected by the season in which individuals were collected, the SCP was significantly affected by the cooling rate of the experiment. Both species had low molecular weight cryoprotective in their hemolymph that could explain their cold-tolerance behavior. Glucose, glycerol, and trehalose were found in A. crassa's hemolymph, only glucose and glycerol were found in E. condorito's . We analyzed the hemolymph proteins and found no seasonal differences in composition for either species and also we detected protein antifreeze activity in the hemolymph from both arthropods. Graphical abstract: fx1 Highlights: Agathemera crassa and E. condorito occasionally are exposed to subzero temperatures. In the Andean Range, cold tolerance responses from arthropods have poorly been studied. Euathlus condorito avoidsfreezing and A. crassa tolerate moderately body ice formation. These strategies could be associated to the presence of hemolymph cryoprotectans.